Characterization of Defect Induced Multilayer Graphene - Marriatyi Morsin; Suhaila Isaak; Marlia Morsin; Yusmeeraz Yusof (International Journal of Electrical and Computer Engineering (IJECE), 2017)
A study of oxygen plasma on multilayer graphene is done with different flow rates. This is to allow a controlled amount of defect fabricated on the graphene. Results from the study showed that the intensity ratio of defect between D peak and G peak was strongly depended on the amount of oxygen flow rate thus affected the 2D band of the spectra. The inter-defect distance LD ≥ 15 nm of each sample indicated that low-defect density was fabricated. The surface roughness of the multilayer graphene also increased and reduced the conductivity of the multilayer graphene.